Impact Assessment of Improved Technology of Mustard Production in Arid Region of Rajasthan: An Econometric Study - Gawaria, K M; Gajja, B L (Annals of Arid Zone, 2016)
The performance of modern technology of mustard cultivation and its impact on the farmer community of arid region of Rajasthan has been assessed through a survey of 40 farmers at Osian tehsil in Jodhpur District using production functions and decomposition analyses. The results suggested that the introduction of improved mustard technology exhibited constant effect in comparison to traditional technology. The total difference in the mustard productivity between modern and traditional technology was estimated to be about 50%. The major component of the productivity gap was due to the difference in varietal component contributing approximately 39%, while remaining 11% was shared by different inputs in terms of differences in their use levels between modern and traditional production technology in this crop. The study suggests that with the adoption of modern technology farmers could harvest better yields from their inputs. Key words: Mustard, production function approach, yield decomposition model, nature of technology change.